Penerapan Diabetes Self-Management Education terhadap Peningkatan Pengetahuan dan Self-Care Management Pasien Diabetes Melitus Tipe II - Mantiri, Sintha; Masi, Gresty Natalia Maria; Fitriani, Fitriani (Mapalus Nursing Science Journal, 2024)
Background: Diabetes mellitus is a chronic disease where the pancreas is unable to produce enough insulin for the body's needs so that it can cause complications such as kidney failure, heart failure, stroke, injury and death. These complications can be minimized by providing education with a diabetes self-management education approach which consists of five pillars of diabetes mellitus management, namely dietary management, physical activity, blood sugar monitoring, medication compliance and foot care. Objective: To implement nursing interventions in the form of self-management education for Mrs. L. P with a medical diagnosis of type two diabetes mellitus. Methods: Case study on Mrs. L. P with a medical diagnosis of type two diabetes mellitus using booklet media. The intervention was given for two sessions. The instrument used is a questionnaire of the level of knowledge and self-care management of diabetes mellitus which has been tested for validity and reliability. Results: After being given the diabetes self-management education intervention, it was found that there was an increase in Mrs. L. P's knowledge which was marked by an increase in the number of correct answers from 17 during the pre-test to 19 during the post-test. In addition, the patient showed an increase in self-care management after being given the intervention which was marked by an increase in the number of scores from 64 when the pre-test increased to 72 when the post-test as well as an increase in skills in foot care, physical activity and eating arrangements. Conclusion: The Implementation of diabetes self-management education can improve knowledge and self-care management in patients with diabetes mellitus.. Keywords: diabetes self-management education; knowledge; self-care management.